The sources and methods used in the creation of the Levy Institute Measure of Economic Well-Being for the United States, 1959-2013 - Ajit Zacharias; Thomas Masterson; Fernando Rios-Avila (Levy Economics Institute of Bard College, 2018)
This paper documents the sources of data used in the construction of the estimates of the Levy Institute Measure of Economic Wellbeing (LIMEW) for the years 1959, 1972, 1982, 1989, 1992, 1995, 2000, 2001, 2004, 2007, 2010, and 2013. It also documents the methods used to combine the various sources of data into the synthetic dataset used to produce each year's LIMEW estimates.
Keywords: D31; C10; H23; I30; 330; Levy Institute Measure of Economic Wellbeing (LIMEW); Statistical Matching; Synthetic Datasets